^aScooby-Doo! Phantom of the knight^h - Learning Company (Novato, CA Learning Company/Mattel Interactive, 2001)
A medieval ghost clad in armor on a fire-breathing dragon. 'Jinkies! It's the Phantom Knight!' Has he kidnapped a princess from this ancient castle? Join Scooby and the gang in the search for suspects to uncover the terrible truth!"--Container
Ages 5-10
1
Keywords: CD.ROM (Children ); Scooby-Doo (Fictitious character)^vInteractive multimedia